Addressing stigma in infectious disease outbreaks: a crucial step in pandemic preparedness - Amy Paterson; Amy Paterson; Piero L. Olliaro; Amanda Rojek (Frontiers in Public Health, 2023)
There is a complex interplay between infectious disease outbreaks and the stigmatization of affected persons and communities. Outbreaks are prone to precipitating stigma due to the fear, uncertainty, moralisation, and abatement of freedoms associated with many infectious diseases. In turn, this stigma hampers outbreak control efforts. Understanding this relationship is crucial to improving coordinated outbreak response. This requires valid and reliable methods for assessing stigma towards and within impacted communities. We propose adopting a cross-outbreak model for developing the necessary assessment tools. A stigma-informed approach must then be integrated into outbreak preparedness and response efforts to safeguard public health and promote inclusivity and compassion in future outbreaks.